Avian Influenza A virus: Bird Flu - Chelsea T. Smartt; C. Roxanne Rutledge-Connelly (EDIS)
ENY-751, a 3-page illustrated fact sheet by Chelsea T. Smartt and C. Roxanne Connelly, provides information about the A strain of the influenza virus in a question-and-answer format. Includes references. Published by the UF Department of Entomology and Nematology, August 2008.